Strategi Bali TV dalam Mempertahankan Eksistensinya sebagai Stasiun Televisi Lokal di Bali - Hermarani, Putu Arina; Amanda Gelgel, Ni Made Ras; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2021)
PT Bali Ranadha Televisi (Bali TV) is the only local television broadcasting institution located in Bali. This study aims to explain the strategic management of Bali TV broadcasting programs in maintaining its existence as a local television station in Bali. The author uses descriptive qualitative research methods with broadcast program strategy management theory and analysis using Niche theory in media ecology. The research results obtained are (1)Bali TV program planning is consistent to create a local broadcast program that implements its vision and mission, (2)Bali TV produces its programs internally around 90% and 10% are the result of cooperation with other parties, (3)The execution of the Bali TV program has broadcast 47 dominant local broadcast programs including information broadcast programs, and (4)Supervision of broadcast programs is not measured by program rating research reports, program evaluations are obtained from audiences and advertisers. Keywords: Bali TV, Private Local Television, Broadcast Program Strategy Management, Local Broadcast Programs.